The helping-effect of dative case - Rothmayr, Antonia (Proceedings of the Amsterdam Colloquium, 2005)
German helfen (help) + DAT cannot be captured by standard applicative analyses. Employing a post-Davidsonian view, the paper derives the different stative/eventive readings of helfen. Eventiveness is tied to DO and BECOME, but not to CAUSE. Helfen is related to other uses of dative in German via Brandt 2003. One of the questions of linguistic theory is how event structure and argument structure interact with each other. This paper argues that event structure can be read off from syntactic structure directly and that the different arguments receive their interpretation because of their position within the structure.